Microwave Synthesis and Biological Activity of some Schiff Base Derives - Rasheed, Rashed Taleb; Ali, Mahammed Shamil; Mansoor, Hadeel Salah; Saadoon, Ali Haadib (Al-Nahrain Journal of Science, 2018)
The organic compounds (L1–L7) have been synthesized by microwave and investigated by different physicochemical techniques. The resulting of the ligands were characterized by FTIR, UV/visible electronic spectra. The Schiff base may be acts as bidentate, tridentate or teradentate ligand, coordinated through deprotonated oxygen or/and azomethine nitrogen atom. The ligands were assayed for antibacterial activity against some pathogenic bacteria: Staphylococcus aureus (gram positive), and Pseudomonas aeruginosa (gram negative), using paper disc method and placing the ligands on surface at nutrient agar. The results show that the L2 and L3 have higher activities rather than other in both lower and higher concentrations against both kind of bacteria Pseudomonas aeruginosa respectively.